LENGTH OF WOUND CHANNELS USING “FORT 12R” AND “AE 790G1” UNDER THE CONDITIONS OF USE OF VARIOUS TEXTILE MATERIALS - Kusliy, Yu.Yu.; Gunas, V.I.; Yaremyna, I.V.; Vakhovskyi, V.V.; Perebetiuk, L.S. (World of Medicine and Biology, 2023)
The spread of firearms among different strata of the population as a result of socio-economic changes, legislative regulation of the right to carry them or the spread of military conflicts requires conducting a series of experimental studies in order to establish the characteristics of injuries that can be caused by modern weapons. The research carried out on non-biological human body simulators covered with different types of textiles using non-lethal pistols “Fort 12R” and “AE 790G1” made it possible to establish that at a shot distance of up to 50 cm, regardless of the type of textile, a defect with a depth of at least 1 cm is formed; defects with a depth of 5 cm do not occur in cases of a shot from a distance of 25 cm or more. When using these guns, the depth of the wound channel can be no more than 6 cm.